Analisis SWOT Terhadap Motivasi Penggunaan Transaksi Non Tunai (E- Money Syariah) oleh Pelaku UMKM - Lola Malihah; Muhammad Yulian Ma'mun; Muhammad Adi Riswan Al-Mubarak; Rizqi Amalia (xxxx-xxxx, 2021)
The necessity of easy-to-use financial services applications emerges as people's needs and mobility in the recent digital era become more complex than before. Users expect Islamic-based electronic money (e-money) applications to provide convenience in their transactions. But the development of these apps has some shortcomings. Among them is that users must connect to a good and stable internet network to run the application properly. In addition, the potential threats of cybercrimes often worry the public, which may reduce their interest in Islamic e-money applications. This study uses a qualitative descriptive approach. It aims to determine the problems in non-cash transactions within Islamic e-money applications by using SWOT analysis. This research obtains data through a combination of observation, interviews, documentation, and triangulation. Thus, this study recommends that Islamic e-money publishers improve application security systems to keep users secure and safe. It also suggests that Islamic financial institutions should expand the education of non-cash transactions and strengthen the promotion of the apps to reach a wider audience from the public and MSMEs businesspeople.